2017
DOI: 10.1002/brb3.854
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines correlate with early exercise attenuating anxiety‐like behavior after cerebral ischemia

Abstract: Background and ObjectiveStroke may cause neuropsychiatric problems, which have negative effects on cognitive functions and behavior. Exercise plays an important role in reducing the occurrence and development of stroke, the concrete mechanism is not fully clarified. In this study, we attempted to determine whether early treadmill exercise attenuates anxiety‐like behavior by regulation of inflammation after brain ischemia.MethodWe subjected adult male rats to middle cerebral artery occlusion (MCAO) for 90 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Proliferation and activation of microglia is a key feature in neurodegenerative disease settings [28]. Our data showing microglia activation following anesthesia and surgery are in line with several studies [29][30][31]. Leakage of peripheral cytokines through blood-brain barrier breakdown might be the main trigger [2].…”
Section: Discussionsupporting
confidence: 88%
“…Proliferation and activation of microglia is a key feature in neurodegenerative disease settings [28]. Our data showing microglia activation following anesthesia and surgery are in line with several studies [29][30][31]. Leakage of peripheral cytokines through blood-brain barrier breakdown might be the main trigger [2].…”
Section: Discussionsupporting
confidence: 88%
“…The therapeutic doses of physical exercise training used in our study were calculated as 40% of this maximum velocity for mild exercise training, which amounted to approximately 15 m/min, and 80% of the maximum velocity for intense exercise training, which was about 32 m/min (Zhang et al, 2012 ; Li F. et al, 2020 ). To further accentuate the difference between the two categories, we reduced the mild exercise group’s speed to a maximum of 12 m/min as done by previous studies (Tian et al, 2013 ; Zhang et al, 2017 ; Tang et al, 2018 ; Li F. et al, 2020 ). For the high-intensity group, we selected 30 m/min because we have employed this speed in our previous work, in which we found that it reduced brain damage (Ding et al, 2006 ), blood-brain barrier dysfunction (Guo et al, 2008 ), and brain inflammation in stroke (Curry et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic doses of physical exercise training used in our study were calculated as 40% of this maximum velocity in the case of mild exercise training, which amounted to approximately 15 m/min, and 80% in the case of intense exercise training, which was about 32 m/min (Zhang et al, 2012 ). To further increase the difference between our categories, we reduced speed in the mild group to a maximum of 12 m/min as previous studies (Tian et al, 2013 ; Zhang P. et al, 2013 ; Zhang et al, 2017 ; Tang et al, 2018 ). For the high-intensity group, we selected 30 m/min because we have employed this speed in previous work, in which we found that it reduced brain damage (Ding et al, 2006 ), blood-brain barrier dysfunction (Guo et al, 2008 ), and brain inflammation in stroke (Curry et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%